Isolation of cellulose-degrading Cellulosimicrobium from larval gut of Protaetia brevitarsis seulensis - Quy Quyen, Phan Thi; Van Anh, Le Thi; Le Han, Ho; Tran-Van, Luan; My Kieu, Tran Thi; Ngoc Thu, Tran Thi; Dong Phuong, Nguyen Thi (Vietnam Journal of Biotechnology, 2023)
Larvae live in soil have been well known for containing abundant microbiota in their gut. This study isolated six bacterial genera from the gut of larvae Protaetia brevitarsis seulensis including Bacillus, Cellulosimicrobium, Microbacterium, Streptomyces, Krasilnikoviella and Isoptericola based on specific media. Among these six genera, Cellulosimicrobium was collected for further analysis of cellulose-degrading features because of the most abundance and less studies up to now. Based on the 16S rDNA gene, the Cellulosimicrobium isolates were classified to C. cellulans, C. aquatile, C. funkei, C. protaetiae that were respectively isolated from four specific media such as modified ISP-2, MRS, modified anaerobic medium, modified fermentation medium. The analysis of their genome proved the presence of genes encoding for chitinases, alkyl resorcinol, and glucosidase in four strains. These cellulose degrading enzymes were useful for textile processing, paper recycling, production of nutritional supplements, food industry, production of alcohol from lignocellulosic materials, and beneficial microorganisms in denitrification and N-cycling in forest ecosystem as well as wastewater process.